The Influence of Sustainability Report, Intellectual Capital, Liquidity, and Firm Size on Firm Value - Fadillah, Shifa Nur; Noormansyah, Irvan (SAN Scientific, 2023)
This study aims to determine the effect of the Sustainability Report (SR), Intellectual Capital, Liquidity, and Firm Size on Firm Value in manufacturing firms listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative methodology and a multiple linear regression data analysis method to analyze the quantitative data. Manufacturing businesses listed on the Indonesia Stock Exchange between 2017 and 2021 comprise the study's population. The purposive sampling method was used to select the sample of 11 manufacturing firms and gave the study a total of 55 observations. The information used in this study is secondary. The methodology for gathering data uses a literature review on the official IDX website (www.idx.co.id). The results of this study prove that (1) the Sustainability Report negatively affects firm value, (2) Intellectual Capital does not affect firm value, (3) Liquidity has no effect on firm value, and (4) Firm size has no effect on firm value.